2006
DOI: 10.1175/jas3713.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Nucleating Aerosol on Florida Storms. Part I: Mesoscale Simulations

Abstract: Toward the end of the Cirrus Regional Study of Tropical Anvils and Cirrus Layer-Florida Area Cirrus Experiment (CRYSTAL-FACE) field campaign held during July 2002, high concentrations of Saharan dust, which can serve as cloud condensation nuclei (CCN), giant CCN (GCCN), and ice-forming nuclei (IFN) were observed over the peninsula of Florida. To investigate the impacts of enhanced aerosol concentrations on the characteristics of convective storms and their subsequent anvil development, sensitivity tests are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
250
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 312 publications
(274 citation statements)
references
References 72 publications
21
250
1
2
Order By: Relevance
“…In the simulations with a low water vapor content, increasing the aerosol concentration had little effect on the concentration of graupel particles. These results are consistent with previous studies [36][37][38][39][40][41][42] in which increasing the initial CCN concentrations reduced the droplet size, enhanced condensation growth, and reduced the efficiency of the collision and coalescence of droplets. This led to more small droplets being transported above the freezing level and enhanced the growth of ice-phase particles under conditions of ample amounts of water vapor.…”
Section: Experimental Designsupporting
confidence: 93%
“…In the simulations with a low water vapor content, increasing the aerosol concentration had little effect on the concentration of graupel particles. These results are consistent with previous studies [36][37][38][39][40][41][42] in which increasing the initial CCN concentrations reduced the droplet size, enhanced condensation growth, and reduced the efficiency of the collision and coalescence of droplets. This led to more small droplets being transported above the freezing level and enhanced the growth of ice-phase particles under conditions of ample amounts of water vapor.…”
Section: Experimental Designsupporting
confidence: 93%
“…The enhancement in evaporation induced by the increase in aerosol concentration develops stronger downdrafts and, when stronger downdrafts descend below the cloud base and collide with environmental flow around the surface, low-level convergence can be intensified. The more intensified domain-averaged low-level convergence generated domain-wide more secondary clouds, inducing the more, stronger domain-averaged updrafts and thus the more domain-averaged condensation, cloud mass and precipitation (Khain et al, 2005;Seifert and Beheng, 2006;van den Heever et al, 2006;van den Heever and Cotton, 2007;Tao et al, 2007;Lee et al, 2008aLee et al, , b, 2009Lee and Feingold, 2010;Storer et al, 2010). Since lowering humidity enables more efficient evaporation, the effect of increases in aerosol concentration on low-level convergence should be stronger at lower humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing aerosol concentration is known to decrease droplet size and thus increase cloud albedo for a given liquid-water content (the first aerosol indirect effect) (Twomey, 1977). They may also suppress precipitation and, hence, alter cloud-water content and lifetime (the second aerosol indirect effect) (Albrecht, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some simulation studies [3][4][5] showed that enhancing the concentration of aerosols resulted in delaying the precipitation start time, stimulating the convection, and forming more big ice particles. Lightning intensity was closely linked with convection intensity.…”
Section: Introductionmentioning
confidence: 99%